ANALISA WAKTU TUNGGU DI LAYANAN ADMINISTRASI AKADEMIK UNIVERSITAS BUNDA MULIA DENGAN METODE SIMULASI - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2017)
Academic Administration Service management continues to be a major challenge for many Universities or school organizations as Universities are required to provide more services with less resources. Short response times for service are essential to avoid disruptions to University’s day to day activities or Academic Administration Service’s facilities. Managers must regularly assess their manpower needs, and ensure that their allocations and operational decisions lead to the best service at the lowest cost. Service staff allocation and response-time in service involves many challenging problems, because the mean and variance of the response-time in service can increase dramatically with traffic intensity, consequently the design for this system has to be able to cope with this complication. This experiment discusses how to use simulation model to improve response-time in service operations. Simulation experiments for analyzing the steady-state behavior of queuing systems over a range of traffic intensities are considered the best method of solution. The technique of simulation consists of taking random samples from the probability distribution which represents the real-world system. In this research the effects of dependent departure intervals on waiting times are examined for a one-station queuing system, and inter-arrival times are compared to a computer-simulated inter-arrival times having dependent arrivals. Significant differences in service times are found due to the mean and variance of the service times.The purpose of this research is to propose a new dynamic-server queuing model to increase system efficiency and customer satisfaction compared with the current practice. Key Words,Interarrival Time, Service Time, and Simulation.